(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
background: Giardia lamblia is one of the commonest human intestinal protozoa, it cosmopolitan and is endemic throughout the world with a wide range of mammalian hosts. Objective: This object aimed to focus on molecular detection of β-Giarin gene of Giardia lamblia in patient with peptic ulcer to investigate an association between Giardia lamblia and Helicobacter pylori infection. Methods: a total of 64 stool sample were collected from patients attending to endoscopy unit (specialized Marjan Hospital for Internal and Cardiac Diseases in Babyoln province) for their peptic ulcer symptoms And were positive for H. pylori. Polymerase chain reaction was achived by primers that targeted the (β-Giardin) gene (218pb) of Giardia lamblia. Results: in this study 64 stool sample were collected from patients with peptic ulcer, Giardia lamblia infection was found in 12 (18.7%) according to direct examination of stool sample, while 21 (32.8%) was positive to giardiasis when used PCR for detection of β-Giardin gene (218pb) ,also the percentage of infection in male was significantly (p <0.05) higher than female with giardiasis infection isolated from peptic ulcer patients and the most frequent symptom was heartburn (15.6%) and diarrhea ( 9.3%), followed by abdominal pain (7.8%). Conclusion: from the results of this study we conclude that Giardia lamblia is high in patients with peptic ulcer. To investigate the causes of peptic ulcer, it should be considered the Giardia lamblia infection as an etiologic factor. This approach will be useful in diagnosis and management of peptic ulcer